Fairness in Fair Dealing on Industrial Design Protection - Sigit Nugroho; Derita Praptirahayu; Mieke Yustia Ayu Ratna Sari (Yuridika, 2021)
Fair dealing is an important element in industrial design legislation. Analysing the concept of fair dealing can help society achieve fairness in protecting industrial design works. Fair dealing means that other parties can use industrial design for education and research purposes as long as it does not prejudice the interests of industrial design rights holders. This study aims to analyse the value of fairness in the concept of fair dealing in industrial design law to be used as guidelines for the rights holders and the public so they do not violate industrial design law and advance the welfare of society. This study uses normative legal research through statutes, conceptual approaches, and primary and secondary legal materials. This study finds that fairness in fair dealing and the protection of industrial design can be achieved by balancing the rights of designers and society. Fairness for both can be achieved if the rights holders and society have opportunities to use and enjoy industrial designs. Industrial design rights holders have limited monopoly rights, and the public can use the results of industrial design in a limited manner for their welfare. This is in line with Aristotle’s observation that justice is given in accordance with values of propriety that are not the same.